Effect of topical honey application along with intralesional injection of glucantime in the treatment of cutaneous leishmaniasis - Moradi Shahram; Jaffary Fariba; Nilforoushzadeh Mohammad; Derakhshan Roya; Haftbaradaran Elaheh (BMC, 2007)
Abstract Background Leishmaniasis is an endemic disease in Iran. Although many treatments have been suggested for this disease, there hasn't been an effective and safe treatment yet. Regarding the healing effect of honey in the chronic ulcers and its reported therapeutic effect in cutaneous leishmaniasis, we performed a study to better evaluate the efficacy of honey in cutaneous leishmaniasis and its final scar. Methods In a prospective clinical trial, 100 patients with confirmed cutaneous leishmaniasis were selected and randomized into 2 groups. Group A were treated with topical honey twice daily along with intralesional injection of glucantime once weekly until complete healing of the ulcer or for maximum of 6 weeks. Group B were treated with intralesional injection of glucantime alone until complete healing of the ulcer or for a maximum of 6 weeks, too. The patients were followed for 4 months. The collected data were analyzed statistically using statistical tests including Chi-square, Mann Whitney and Kaplan - Mayer tests. Results In this study, 45 patients that had cutaneous leishmaniasis were treated with intralesional glucantime alone and 45 patients were treated with topical honey and glucantime . Ten patients left out the study. In the glucantime alone treated group, 32 patients (71.1%) had complete cure whereas in the group treated with both glucantime & topical honey, 23 patients (51.1%) achieved complete cure. This difference was significant statistically (p = 0.04). Conclusion Further studies to better clarify the efficacy of honey in cutaneous leishmaniasis is needed. We suggest that in another study, the efficacy of honey with standardized level of antibacterial activity is evaluated against cutaneous leishmaniasis.